Challenges impeding the successful implementation of early childhood development programmes in South Africa: Implications for practice - Makhubele, J. C; Baloyi, T. V (Gender & Behaviour, 2018)
The purpose of this paper is to discuss, debate, and discourse the stumbling blocks that impede the proper implementation of early childhood development programmes in South Africa. This paper used qualitative methodology. In this study, non-probability sampling was used and, specifically, purposive sampling. The following challenges associated with early childhood development programmes were identified: poor infrastructure; inadequate training of early childhood development educators; and poor financial support, monitoring, and evaluation. The following have been recommended to bolster early childhood development programmes: increase the number of trained early childhood development educators; make sufficient funding available to early childhood development centres; mobilise local funding; adopt various means of strengthening the proper implementation of the early childhood development programmes; and monitor early childhood development services.
Article published in the Gender & Behaviour, vol 16(1), 10773 - 10783
Keywords: Early childhood development programmes; Infrastructure; Funding; Skills gap; Competency; Structural problems; Early childhood education-Activity programs--South Africa